Antibacterial compatilizer as well as preparation method and application thereof

By using graft-modified polyphosphazene microspheres loaded with nanometal oxide antibacterial agent in nylon materials, the antibacterial properties and compatibility problems of nylon materials are solved, and the good compatibility and long-term effect of antibacterial agents and materials are achieved. The effect improves the mechanical properties and service life of the material.

CN119241855AInactive Publication Date: 2025-01-03NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411776414.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing nylon materials lack antibacterial properties, poor compatibility and high cost when adding antibacterial agents, and inorganic antibacterial agents are prone to fall out during use, resulting in antibacterial failure.

Method used

Polyolefin elastomer, grafted modified polyphosphazene microspheres and nanometal oxides are used as antibacterial agents, and the antibacterial agent with core-shell structure is formed through the esterification reaction of graft monomers and polyphosphazene microspheres, and Extrusion grafting with POE and nylon materials to improve compatibility and antibacterial properties.

Benefits of technology

It improves the antibacterial properties and long-lasting performance of nylon materials, enhances the mechanical properties of nylon composite materials, simplifies production processes and reduces costs, and avoids the problem of inorganic antibacterial agent removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241855A_ABST
    Figure CN119241855A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial compatilizer as well as a preparation method and application thereof, and relates to the technical field of high polymer materials. The antibacterial compatilizer I is prepared from a polyolefin elastomer, an antibacterial agent, a first grafting monomer and an initiator through a cross-linking reaction; the antibacterial agent and the first grafting monomer are respectively grafted on a long chain of the polyolefin elastomer; the antibacterial agent is prepared by carrying out esterification reaction on a second grafting monomer and hydroxyl on the surface of the nano metal oxide coated polyphosphazene microsphere; the first grafting monomer is maleic anhydride or cis-1, 2, 3, 6-tetrahydrophthalic anhydride, and the second grafting monomer is maleic anhydride or cis-1, 2, 3, 6-tetrahydrophthalic anhydride. According to the invention, the nano metal oxide coated polyphosphazene microspheres are grafted with the grafting monomer, and then the grafted nano metal oxide coated polyphosphazene microspheres, the POE and the grafting monomer are subjected to a cross-linking reaction, so that the compatilizer and the antibacterial agent form an integral structure, the problem of poor compatibility of the antibacterial agent and a nylon material is solved, and the problem of short antibacterial time of the nylon material is solved; therefore, the nylon material has antibacterial performance in the whole service period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an antibacterial compatibilizer and a preparation method and application thereof. Background Art

[0002] Nylon material, one of the five major engineering plastics, is a condensation-type polymer compound with repeating units of amide groups in the main chain of the molecule. Thanks to the hydrogen bonding effect in the main chain structure of the polyamide molecule and the synergistic effect of a certain length of saturated alkane carbon chain, it has excellent mechanical properties, processing properties, chemical corrosion resistance and dimensional stability. It is widely used in home building materials, electronic appliances, auto parts, clothing and textiles, packaging, medical and other fields.

[0003] With the development of science and technology and the improvement of living standards, the requirements for materials are getting higher and higher. Based on the widespread application of nylon materials, there are increasingly higher requirements for its service life in specific occasions and the "self-cleaning" function of auxiliary plastic products. However, the existing industrialized nylon material products themselves do not have antibacterial properties. Taking the most common glass fiber reinforced nylon material in practical applications as an example, it is often necessary to add antibacterial additives to make it antibacterial. However, the compatibility of additive antibacterial additives with glass fiber and nylon itself is poor, and additional compatibilizers are needed to increase the compatibility and dispersion between the three.

[0004] On the one hand, the wide application of nylon materials also places higher requirements on the safety performance of nylon materials themselves. Therefore, when adding antibacterial agents to give nylon materials antibacterial properties, in addition to compatibility, the safety performance of the antibacterial agents themselves also has higher requirements. Among the existing inorganic antibacterial agents, nanosilver is the most widely used. For example, Chinese invention patent CN 112841221A provides a mesoporous core-shell structure polyphosphazene silver-loaded microsphere and its preparation method and application. The mesoporous core-shell structure polyphosphazene microspheres are loaded with nanosilver particles to obtain an antibacterial agent with antibacterial properties, which can improve the long-term bactericidal performance of the antibacterial agent; however, the cost of nanosilver particles limits the scope of its use.

[0005] On the other hand, inorganic metal oxide antibacterial materials, such as MgO, also exhibit excellent antibacterial properties under dark conditions. The antibacterial mechanism of MgO lies in non-ROS physical damage. MgO has good biocompatibility, which enables it to directly contact and interfere with bacterial metabolism, ultimately leading to cell death and achieving the purpose of sterilization. In addition, due to its excellent properties such as low cost, wide availability, non-toxicity and environmental friendliness, it has a wide range of application prospects. However, directly using it as an antibacterial agent in nylon materials, on the one hand, has the same problem of poor dispersibility as other inorganic antibacterial agents. On the other hand, with the use of nylon materials, the inorganic antibacterial agent will gradually escape from the nylon material, resulting in its antibacterial failure.

[0006] The present invention is based on the prior art and further improves it, providing a compatibilizer with antibacterial function, which reduces the types of additives added to the nylon material, simplifies the production process, reduces the production cost, and eliminates the interface bonding effect between the nylon material and the antibacterial agent, thereby improving the antibacterial performance and long-lasting antibacterial performance of the nylon material. Summary of the invention

[0007] In order to overcome the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an antimicrobial compatibilizer and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0008] To achieve the above objectives, the present invention provides the following technical solutions.

[0009] One aspect of the present invention provides an antimicrobial compatibilizer, which consists of a polyolefin elastomer, a first antimicrobial agent, a first grafting monomer and an initiator.

[0010] Preferably, the first antimicrobial agent is grafted modified polyphosphazene microspheres (Yg-[XO@PZs]).

[0011] Preferably, the first grafting monomer is cis-1,2,3,6-tetrahydrophthalic anhydride.

[0012] Specifically, the first antibacterial agent is cis-1,2,3,6-tetrahydrophthalic acid grafted polyphosphazene microspheres (Yg-[XO@PZs]).

[0013] As a preferred embodiment, the first antibacterial agent is prepared by esterification reaction between the second grafting monomer and the hydroxyl groups on the surface of nano-metal oxide@polyphosphazene microspheres.

[0014] Preferably, the initiator is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, and diisopropyl peroxydicarbonate.

[0015] More preferably, the initiator is selected from dicumyl peroxide.

[0016] Preferably, the added amount of the first grafting monomer accounts for 2.5-5wt% of the polyolefin elastomer.

[0017] Preferably, the added amount of the first antibacterial agent accounts for 2.5-5wt% of the polyolefin elastomer.

[0018] Preferably, the added amount of the initiator is 0.5-1 wt % of the polyolefin elastomer.

[0019] As a preferred embodiment, the preparation method of the first antibacterial agent provided by the present invention comprises the following specific steps: S1. adding hexachlorocyclotriphosphazene (HCCP), resveratrol (RSV) and a second antimicrobial agent (XO) into an organic solvent, and uniformly dispersing them by ultrasonic cleaning to obtain a mixed solution; S2. slowly adding an acid binding agent to the above mixed solution, and obtaining a polyphosphazene microsphere (PZs) solution under the condition of increasing temperature and ultrasonication; S3. Add the second grafting monomer and the catalyst to the polyphosphazene microsphere solution and heat to perform a catalytic reaction to obtain a reaction product. After washing and drying, the final purified product, i.e., the polyphosphazene microspheres grafted with the second grafting monomer (Yg-XO@PZs), is obtained.

[0020] In some specific embodiments, the second antimicrobial agent in S1 is nano metal oxide.

[0021] Preferably, the second antibacterial agent is an inorganic antibacterial agent, specifically, the inorganic antibacterial agent is any one or more combinations of nano-MgO, nano-CuO, nano-ZnO, and nano-TiO2.

[0022] Preferably, the ultrasonic cleaner has a power of 300W and a frequency of 40Hz.

[0023] Preferably, the mass ratio of hexachlorocyclotriphosphazene, resveratrol and the second antibacterial agent is 1:(1-3):(1-3).

[0024] Preferably, the organic solvent is selected from one or more of tetrahydrofuran, methanol, acetonitrile, ethanol, acetone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0025] In some specific embodiments, the acid binding agent in S2 is selected from a combination of one or more of triethylamine, pyridine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, potassium carbonate, ammonium carbonate and sodium carbonate; most preferably, the acid binding agent is triethylamine.

[0026] Preferably, the polyphosphazene microspheres are nano-metal oxide@polyphosphazene microspheres (XO@PZs) with a core-shell structure and a size of micrometers.

[0027] In some specific embodiments, the catalyst in S3 is phthalic acid.

[0028] Preferably, the second grafting monomer is maleic anhydride or cis-1,2,3,6-tetrahydrophthalic anhydride.

[0029] Most preferably, the second grafting monomer is the same as the first grafting monomer to enhance the compatibility of the first antimicrobial agent with the antimicrobial compatibilizer, while reducing the types of raw materials and simplifying the operating procedures.

[0030] Preferably, the washing and drying process comprises washing the reaction product with ethanol and deionized water for three times respectively, and then vacuum drying the washed product at 60° C. for 24 hours.

[0031] As a preferred embodiment, the antimicrobial compatibilizer components are as follows, in parts by mass: 100 parts of polyolefin elastomer, 2.5 to 5 parts of antimicrobial compatibilizer, 2.5 to 5 parts of first grafting monomer, and 0.5 to 1 part of initiator.

[0032] Preferably, the second grafting monomer is the same as the first grafting monomer.

[0033] As another object of the invention, the present invention also provides a method for preparing the aforementioned antibacterial compatibilizer, comprising adding a polyolefin elastomer, a first antibacterial agent, a first grafting monomer and an initiator into a high-speed mixer for mixing; then, feeding the materials into a twin-screw extruder through a feeding port, setting reaction conditions for reaction and extrusion; finally, cooling and pelletizing to obtain a grafted product, namely Y'-g-POE-g-(Yg-[XO@PZs]).

[0034] Preferably, the reaction conditions include a reaction temperature of 200-220° C. and a screw speed of 200-300 rpm.

[0035] Preferably, the feeding speed is 10-20 rpm.

[0036] As one of the purposes of the invention, the present invention also provides the use of the aforementioned antibacterial compatibilizer in the preparation of modified nylon materials.

[0037] As one of the purposes of the invention, the present invention also provides a modified nylon material, comprising the aforementioned antibacterial compatibility agent, nylon and a toughening agent; the toughening agent is glass fiber.

[0038] Preferably, the modified nylon material comprises, by weight, 50-70 parts of nylon, 25-40 parts of glass fiber, 3-9 parts of the antibacterial compatibilizer and 0.2-0.4 parts of antioxidant.

[0039] Preferably, the preparation method of the modified nylon material comprises: placing nylon, glass fiber, antibacterial compatibilizer, and antioxidant in a high-speed mixer for mixing; placing the mixed mixture in a twin-screw extruder, setting the extrusion temperature to 240-280°C, the screw speed to 300-400 rpm, and the feed speed to 10-20 rpm. The extrudate is cooled in a cooling water tank and pelletized to obtain modified nylon pellets.

[0040] Preferably, the nylon is nylon 66 or nylon 6; and the antioxidant is antioxidant 1098.

[0041] As the most preferred embodiment, the first grafting monomer and the second grafting monomer selected in the present invention are both cis-1,2,3,6-tetrahydrophthalic anhydride; cis-1,2,3,6-tetrahydrophthalic anhydride is used as the grafting monomer, the melting point of the compound is 101~102℃, and the boiling point is 234.6℃‌‌. The monomer has a higher melting point and boiling point than maleic anhydride, and in particular, can meet the temperature requirements of melt extrusion during the grafting process, avoiding the volatilization and degradation of the anhydride monomer.

[0042] The technical effects of the technical solution of the present invention are as follows: 1. The present invention selects an inorganic antibacterial agent (nanometallic oxide) as an antibacterial agent to be loaded in polyphosphazene microspheres to form an antibacterial agent with a core-shell structure, and then grafts it with a grafting monomer to make it have good compatibility with POE, nylon materials, etc. On the one hand, it solves the problem of short antibacterial time of nylon materials, improves its antibacterial performance, and enables nylon materials to have antibacterial performance throughout the service life. On the other hand, it also solves the compatibility problem between the inorganic antibacterial agent itself and the nylon material.

[0043] 2. By adopting the technical solution of the present invention, the compatibilizer prepared by grafting POE with cis-1,2,3,6-tetrahydrophthalic anhydride, the anhydride monomer can react chemically with the terminal amino group of the polyamide, thereby improving the interfacial bonding force between the dispersed phase and the matrix; at the same time, the anhydride group can also react with the hydroxyl group and other groups on the surface of the glass fiber, and the polyolefin at the other end is entangled with the nylon chain, thereby also improving the interfacial bonding between the glass fiber and the nylon, thereby improving the mechanical properties of the nylon composite material.

[0044] 3. The antibacterial compatibilizer provided by the technical solution of the present invention is applied to the modification of thermoplastics. The provided compatibilizer has the dual functions of a compatibilizer and an antibacterial agent. When applied to nylon materials, it can be completely integrated with the nylon materials, avoiding the problem of short antibacterial effectiveness caused by the inorganic antibacterial agent being applied to the nylon material and escaping from the material. The preparation method has the advantages of simple operation and easy control, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the reaction principle of the antibacterial agent TA-g-[MgO@PZs] prepared in Example 1 of the present invention.

[0046] Figure 2 Schematic diagram of the reaction principle of the antibacterial agent TA-g-POE-TA-g-[MgO@PZs] prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0048] The present invention provides a method for preparing an antimicrobial compatibilizer, the specific steps of which include: S1. adding hexachlorocyclotriphosphazene (HCCP), resveratrol (RSV) and an inorganic antimicrobial agent (XO) into an organic solvent, and uniformly dispersing them by ultrasonic cleaning to obtain a mixed solution; S2. slowly adding an acid binding agent to the above mixed solution, and obtaining a polyphosphazene microsphere (PZs) solution under the condition of increasing temperature and ultrasonication; S3. adding a second grafting monomer and a catalyst to the polyphosphazene microsphere solution and heating to perform a catalytic reaction to obtain a reaction product, and washing and drying to obtain a final purified product, namely, the second grafting monomer grafted polyphosphazene microsphere (Yg-[XO@PZs]); S4. Weigh the polyolefin elastomer (POE), antimicrobial agent, first grafted monomer, and initiator according to the set ratio and mix them in a high-speed mixer. After mixing, add the materials to the feed port, add them to the twin-screw extruder from the feed port at the set speed, and perform reaction extrusion according to the set conditions. The extrudate is cooled in a cooling water tank and pelletized to obtain the product of POE grafted antimicrobial agent and first grafted monomer, which is the antimicrobial compatibilizer (Y'-g-POE-(Yg-[XO@PZs])).

[0049] The antibacterial compatibilizer provided by the present invention is also grafted with an antibacterial agent TA-g-[XO@PZs], wherein the antibacterial component is a polyphosphazene microsphere (XO@PZs) with a micron-scale core-shell structure loaded with nano-metal oxides, and the shell material thereof is composed of resveratrol, which is a polyhydroxystilbene natural antioxidant with significant antibacterial effect, and the core material component nano-metal oxide also has strong antibacterial properties, and it has a slow release effect when stored in the core. With the help of the hydrogen bond interaction between its own polyhydroxy structure and the nylon amide bond and the mutual entanglement between POE and the nylon molecular chain, it can obtain good dispersibility in the nylon system, thereby facilitating its long-acting sustained-release antibacterial effect.

[0050] The compatibilizer provided by the above technical solution can be applied to thermoplastic plastics.

[0051] In the process of co-processing the compatibilizer and the thermoplastic, processing aids and modifiers conventional in the art are also used, such as flame retardants, lubricants, ultraviolet absorbers, antioxidants, fillers, etc.

[0052] The test methods and standards for the performance parameters of the following embodiments and comparative examples of the present invention are as follows: (1) Grafting rate: The grafting rate of TA in the grafted product was calculated by acid-base titration.

[0053] Weigh 1.0 g of the purified grafted product, heat and reflux in 50 ml of xylene solution for 30 min to fully dissolve the grafted product, then titrate with a 0.1 mol / L KOH-ethanol standard solution, use colorless phenolphthalein test solution as an indicator, add dropwise under continuous stirring, and record the volume V1 of the KOH-ethanol standard solution used when the solution turns red. Then back-titrate with a CH3COOH-ethanol standard solution of the same concentration, stop titrating when the solution changes from red to colorless, and record the volume V2 of the CH3COOH standard solution used. Measure three times according to the above experimental steps and take the average value, and calculate the grafting rate GR according to the following formula: ; Wherein, C is the concentration of KOH and CH3COOH-ethanol standard solution (mol / L); M is the relative molecular weight of TA (g / mol); and m is the mass of the grafted sample to be titrated (g).

[0054] (2) Melt index: Refer to GB / T 3682-2000 standard, use a melt flow rate meter to measure the mass of the sample flowing out of the die of the special equipment within ten minutes, which is the melt index. The test conditions are as follows: temperature 230℃, weight 2.16kg (230℃*2.16 kg). Each sample is tested five times and the average value is taken.

[0055] (3) Mechanical properties: The tensile strength was tested according to ISO 527-1 / -2, the flexural strength and flexural modulus were tested according to ISO 178, and the simply supported beam notched impact strength was tested according to ISO 179 / 1eA.

[0056] (4) Antibacterial performance: Refer to QB / T 2591-2003A "Test methods and antibacterial effects of antibacterial plastics", and use Escherichia coli ( Escherichia coli ) ATCC 25922 and Staphylococcus aureus ( Staphylococcus aureus )ATCC 6538.

[0057] The technical solution of the present invention is described in detail below through specific embodiments.

[0058] Example 1 The preparation method of the antibacterial compatibilizer provided in this embodiment takes nano magnesium oxide as an example. Specifically, the synthesis steps are as follows: Figure 1 ,include: Hexachlorocyclotriphosphazene (HCCP) and resveratrol (RSV) react to generate hydrogen chloride (HCl), which is adsorbed by the acid-binding agent to generate the corresponding crystalline salt, accelerating the polycondensation reaction. Through the nucleophilic substitution reaction between the hydroxyl group and the P-Cl bond, a large number of oligomers begin to appear and aggregate to form primary core particles. Due to the low surface energy of the particles, the primary nucleated particles will automatically diffuse to the surface of the nano-magnesium oxide particles, and the primary core particles coated on the nano-magnesium oxide will continuously undergo cross-linking reactions until uniform nanospheres (MgO@PZs) are formed. The surface of the polyphosphazene microspheres has a large number of hydroxyl groups. The grafted monomer cis-1,2,3,6-tetrahydrophthalic anhydride undergoes an esterification reaction with the surface hydroxyl groups and is grafted on the surface of the polyphosphazene microspheres to obtain the first grafted product TA-g-[MgO@PZs].

[0059] Further, see Figure 2 The first grafting product TA-g-[MgO@PZs] and the grafting monomer respectively undergo a second grafting reaction with the double bonds in POE. The first grafting product TA-g-[MgO@PZs] and the grafting monomer are cross-linked on the long chain of POE to obtain TA-g-POE-TA-g-[MgO@PZs]. On the one hand, the double bonds of POE are eliminated and its reactivity is reduced. On the other hand, polyphosphazene microspheres with antibacterial activity are grafted on POE to realize an integrated structure formed by the antibacterial agent and the compatibilizer. When it is applied to thermoplastic resin materials such as nylon, the antibacterial compatibilizer reacts chemically with the terminal amino group of polyamide, thereby improving the interfacial bonding force between the dispersed phase and the matrix. At the same time, the anhydride group in this component can also react with the hydroxyl group and other groups on the surface of the glass fiber. The polyolefin at the other end is entangled with the nylon chain, thereby improving the interfacial bonding between the glass fiber and nylon and improving the toughening effect of the glass fiber.

[0060] Specifically, the preparation steps of this embodiment include: Weigh 0.4 g hexachlorocyclotriphosphazene (HCCP), 0.53 g resveratrol (RSV), and 0.4 g nano-MgO and dissolve them in 500 mL acetonitrile. Ultrasonicate them in an ultrasonic cleaner. After the reagents are dissolved in acetonitrile, slowly add 10 ml triethylamine. Ultrasonicate them in an ultrasonic cleaner (300W, 40Hz) at 55 °C for 6 hours to obtain core-shell structured MgO@PZs microspheres. Add 0.18 g cis-1,2,3,6-tetrahydrophthalic anhydride (TA) and heat to 80 °C. Use phthalic acid to catalyze the reaction to obtain the antibacterial agent TA-g-[MgO@PZs]. Wash them with ethanol and deionized water three times respectively, and place the washed product under vacuum drying at 60 °C for 24 hours to obtain the final purified product.

[0061] Weigh 100 parts of polyolefin elastomer, 3 parts of cis-1,2,3,6-tetrahydrophthalic anhydride, 3 parts of antibacterial agent (TA-g-[MgO@PZs]), and 0.6 parts of DCP initiator, and mix them in a high-speed mixer. After mixing, add the materials to the feed port, set the feed speed to 10 rpm, the processing temperature to 210℃, and the temperature settings of each section of the twin-screw extruder are: 170℃, 180℃, 190℃, 200℃, 205℃, 205℃, 210℃, 210℃, 190℃, and the screw speed is 200 rpm. The extrudate is cooled in a cooling water tank and pelletized to obtain the grafted product, which is recorded as antibacterial compatibilizer 1#.

[0062] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0063] Example 2 The preparation method of the antibacterial compatibilizer provided in this embodiment, the composition ratio of each component and the preparation method are basically the same as those in Example 1, the difference being that the inorganic antibacterial agent added in this embodiment is nano-CuO.

[0064] The obtained product was recorded as antibacterial compatibilizer 2#.

[0065] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0066] Example 3 The component ratio and preparation method of the antimicrobial compatibilizer of this embodiment are basically the same as those of Example 1, except that the amount of initiator used in this embodiment is 0.5 parts, and the obtained product is recorded as antimicrobial compatibilizer 3#.

[0067] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0068] Example 4 The component ratio and preparation method of the antibacterial compatibilizer of this embodiment are basically the same as those of Example 1, except that the grafting monomer in this embodiment includes 2.5 parts of cis-1,2,3,6-tetrahydrophthalic anhydride and 2.5 parts of antibacterial agent TA-g-[MgO@PZs]); the obtained grafted product is recorded as antibacterial compatibilizer 4#.

[0069] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0070] Example 5 The component ratio and preparation method of the antibacterial compatibilizer in this embodiment are basically the same as those in Example 1, except that the processing temperature in this embodiment is 200°C, and the temperature settings of each section of the twin-screw extruder are: 160°C, 170°C, 180°C, 190°C, 195°C, 195°C, 200°C, 200°C, 190°C.

[0071] The obtained grafted product was recorded as antibacterial compatibilizer 5#.

[0072] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0073] Example 6 The component ratio and preparation method of the antimicrobial compatibilizer of this embodiment are substantially the same as those of Example 1, except that the screw speed in this embodiment is 250 rpm.

[0074] The obtained grafted product was recorded as antibacterial compatibilizer 6#.

[0075] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0076] The compatibilizers prepared in Example 1 (compatibilizer 1#), Example 2 (compatibilizer 2#), Example 5 (compatibilizer 5#), Example 6 (compatibilizer 6#), Comparative Examples 1 to 3 (compatibilizer 1'# to compatibilizer 3'#) were applied to glass fiber reinforced nylon 66 system, as follows.

[0077] Example 7 This embodiment provides a modified nylon material, and the specific preparation steps include: Weigh 67 parts of nylon 66, 30 parts of glass fiber, 3 parts of antibacterial compatibilizer 1# obtained in Example 1, and 0.3 parts of antioxidant 1098 and put them into a high-speed mixer for mixing. After mixing, place them in a twin-screw extruder, set the extrusion temperature to 270°C, the screw speed to 400 rpm, and the feed speed to 20 rpm. After the extrudate is cooled in a cooling water tank, it is pelletized to obtain modified nylon pellets, and injection molding is used to obtain test specimens. The mechanical properties test results are listed in Table 2.

[0078] Example 8 The preparation method of the modified nylon material in this embodiment is substantially the same as that in embodiment 7, except that the antibacterial compatibilizer in this embodiment is selected from the antibacterial compatibilizer 2# obtained in embodiment 2. The mechanical property test results are listed in Table 2.

[0079] Example 9 The preparation method of the modified nylon material in this embodiment is substantially the same as that in embodiment 7, except that the antibacterial compatibilizer in this embodiment is selected from the antibacterial compatibilizer 5# obtained in embodiment 5. The mechanical properties test results are listed in Table 2.

[0080] Example 10 The preparation method of the modified nylon in this embodiment is substantially the same as that in embodiment 7, except that the antibacterial compatibilizer in this embodiment is selected from the antibacterial compatibilizer 6# obtained in embodiment 6. The mechanical properties test results are listed in Table 2.

[0081] Comparative Example 1 The component ratio and preparation method of the antimicrobial compatibilizer in this comparative example are substantially the same as those in Example 1, except that the amount of the initiator in this comparative example is 1.2 parts.

[0082] The obtained grafted product was recorded as antimicrobial compatibilizer 1'#.

[0083] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0084] Comparative Example 2 The component ratio and preparation method of the compatibilizer in this comparative example are basically the same as those in Example 1, except that the processing temperature in this comparative example is 230°C, and the temperature settings of each section of the twin-screw extruder are: 170°C, 180°C, 190°C, 200°C, 220°C, 220°C, 230°C, 230°C, 230°C, and 220°C.

[0085] The obtained grafted product was recorded as antimicrobial compatibilizer 2'#.

[0086] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0087] Comparative Example 3 The component ratio and preparation method of the antimicrobial compatibilizer in this comparative example are substantially the same as those in Example 1, except that the screw speed in this comparative example is 350 rpm.

[0088] The obtained grafted product was recorded as antimicrobial compatibilizer 3'#.

[0089] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.

[0090] Comparative Example 4 The preparation method of the modified nylon material in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the antibacterial compatibilizer 1'# obtained in Comparative Example 1. The mechanical property test results are listed in Table 2.

[0091] Comparative Example 5 The preparation method of the modified nylon in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the antibacterial compatibilizer 2'# obtained in Comparative Example 2. The mechanical properties test results are listed in Table 2.

[0092] Comparative Example 6 The preparation method of the modified nylon in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the antibacterial compatibilizer 3'# obtained in Comparative Example 3. The mechanical properties test results are listed in Table 2.

[0093] Comparative Example 7 This comparative example is basically the same as Example 7, except that in this comparative example, the antibacterial compatibilizer is replaced by 3 parts of TA-g-[MgO@PZs] antibacterial agent.

[0094] The test results of various properties are listed in Table 2, and the test results of antibacterial properties are listed in Table 3.

[0095] Comparative Example 8 This comparative example is basically the same as Example 7, except that the antibacterial compatibilizer is replaced by 3 parts of MgO@PZs antibacterial agent in this comparative example. The test results of various properties are listed in Table 2, and the test results of antibacterial properties are listed in Table 3.

[0096] Comparative Example 9 This comparative example is substantially the same as Example 7, except that no antimicrobial compatibilizer is added in this comparative example. The mechanical properties test results are listed in Table 2.

[0097] Table 1 Raw material composition, processing conditions, grafting rate and melt index of each embodiment and comparative example

[0098] Comparing Example 1 and Example 4, it can be seen that the higher the content of the grafted monomer, the higher the grafting rate, mainly because the increase in the monomer content can increase the number of effective collisions between it and the grafted resin free radicals, increase the collision probability, and thus improve the grafting rate. It can be seen from Examples 1, 3 and Comparative Example 1 that with the increase in the amount of initiator added, the grafting rate shows a development trend of first increasing and then decreasing. It is attributed to the fact that the increase of initiator within a certain range is conducive to inducing polymer macromolecules to produce more free radicals, increasing the number of grafting sites on the macromolecular chain, thereby increasing the contact probability with the monomer. However, when the amount of initiator added exceeds a certain limit, it will cause the free radical concentration to be too large, resulting in an intensification of the coupling reaction between the free radicals, which will hinder the grafting reaction between the macromolecular free radicals and the monomer.

[0099] It can be seen from Example 1, Example 5 and Comparative Example 2 that the grafting rate also shows a trend of increasing first and then decreasing with the increase of processing temperature. When the temperature is low, the decomposition rate of the initiator DCP is slow, and the grafting reaction rate is low; when the temperature is high, the decomposition rate of DCP increases, which triggers the generation of more macromolecular free radicals, thereby improving the grafting efficiency; when the temperature is too high, excessive macromolecular free radicals are triggered, which easily leads to side reactions such as cross-linking and coupling, thereby inhibiting the grafting reaction.

[0100] It can be seen from Example 1, Example 6 and Comparative Example 3 that when the screw speed is 200 rpm, the grafting rate of the system is the highest. When the screw speed is increased to 350 rpm, part of the initiator will be squeezed out before it has time to decompose and take effect, which is equivalent to a reduction in the effective content of the initiator participating in the reaction, resulting in a significant decrease in the grafting rate.

[0101] Table 2 Test results of various properties of modified nylon resins in various embodiments and comparative examples

[0102] Table 3 Antibacterial performance test results of modified nylon resins in various embodiments and comparative examples

[0103] From the test data results in Table 2 and Table 3, it can be seen that the toughness and antibacterial properties of the glass fiber reinforced nylon 66 system (Example 7-Example 11) with a higher grafting rate of antibacterial compatibilizer are better, and the antibacterial rate shows a gradual upward trend over time, indicating that the antibacterial component has a sustained release effect. It is attributed to the fact that the antibacterial compatibilizer with a higher grafting rate grafts more antibacterial components and anhydride components, which can greatly improve the compatibility between glass fiber, nylon and antibacterial compatibilizer in the glass fiber system, thereby playing a synergistic role. On the contrary, the reduction of the grafting rate (Comparative Example 4-Comparative Example 7) causes a decrease in compatibility and a weakening of the antibacterial performance. It can be seen from Comparative Examples 8 to 9 that without the support of the POE-g-TA carrier, the antibacterial component cannot be well dispersed in the glass fiber reinforced nylon system, resulting in low antibacterial properties; in particular, in Comparative Example 8, the antibacterial agent MgO@PZs is directly added to the system, the compatibility of the antibacterial agent with nylon and glass fiber is poor, and the mechanical strength and toughness of the nylon material are significantly lower than those in Example 7. Obviously, MgO@PZs is completely incompatible with the nylon matrix material, which also shows that grafting MgO@PZs with TA and then grafting it with POE can not only provide antibacterial properties for the nylon material, but also improve the mechanical properties of the nylon material.

[0104] The disclosures of all patent and non-patent literature cited herein are incorporated herein by reference in their entirety.

[0105] As used in the invention, the terms "comprise", "include", "contain", "cover", "have", "with" or any other variation thereof are intended to cover non-exclusive inclusions. For example, a process, method, article or device that includes a list of elements is not necessarily limited to those elements, but may include other elements that are not explicitly listed or inherent to the process, method, article or device. In addition, unless expressly indicated to the contrary, "or" refers to an inclusive "or" rather than an exclusive "or". For example, conditions A or B satisfy any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). The phrase "one or more" is intended to cover non-exclusive inclusions. For example, one or more A, B and C, means any of the following: A alone, B alone, C alone, a combination of A and B, a combination of B and C, a combination of A and C, or a combination of A, B and C.

[0106] In addition, "a" or "an" is used to describe the elements and components described herein. This is done only for convenience and to provide a general sense of the scope of the invention. This description should be understood to include one or at least one, one or at least one, and the singular also includes the plural, unless it is obvious that it is intended otherwise.

[0107] Unless otherwise defined, the meaning of all technical and scientific terms used herein is the same as that generally understood by those of ordinary skill in the art to which the present disclosure belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the disclosed composition embodiments, suitable methods and materials are described below. Unless citing a specific paragraph, all publications, patent applications, patents and other references mentioned herein are incorporated herein by reference in their entirety. If a conflict occurs, this specification and the definitions included therein shall prevail. In addition, materials, methods and examples are illustrative only, and not restrictive.

[0108] The technical scheme of the present invention, its implementation process and principle, etc. will be further explained through specific embodiments as follows. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the reagents and raw materials used in the following examples are commercially available, and the test methods for which specific conditions are not specified are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers. In addition, unless otherwise specified, the experimental methods, detection methods, and preparation methods disclosed in the present invention all adopt conventional techniques in the art. These technologies have been fully described in the existing literature.

[0109] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or by being able to achieve the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.

Claims

1. An antimicrobial compatibilizer, characterized in that: The method is prepared by cross-linking a polyolefin elastomer, a first antimicrobial agent, a first grafting monomer and an initiator; The first antibacterial agent and the first grafting monomer are respectively grafted onto the long chain of the polyolefin elastomer.

2. The antimicrobial compatibilizer according to claim 1, characterized in that: The amount of the first grafting monomer added is 2.5-5wt% of the polyolefin elastomer; The first grafting monomer is cis-1,2,3,6-tetrahydrophthalic anhydride; And / or, the initiator is at least one selected from dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, and diisopropyl peroxydicarbonate; and / or, the first antimicrobial agent is added in an amount of 2.5-5wt% of the polyolefin elastomer; The first antibacterial agent is grafted modified nano metal oxide@polyphosphazene microspheres.

3. The antimicrobial compatibilizer according to claim 2, characterized in that: The first antibacterial agent is prepared by esterification reaction between the second grafting monomer and the surface hydroxyl groups of nano-metal oxide@polyphosphazene microspheres; And / or, the second grafting monomer is maleic anhydride or cis-1,2,3,6-tetrahydrophthalic anhydride.

4. The antimicrobial compatibilizer according to any one of claims 1 to 3, characterized in that: The preparation method of the first antibacterial agent specifically comprises: S1. adding hexachlorocyclotriphosphazene, resveratrol and a second antibacterial agent to an organic solvent, and uniformly dispersing the mixture by ultrasonic cleaning to obtain a mixed solution; S2. Slowly adding an acid binding agent to the mixed solution, heating and ultrasonicating to obtain a polyphosphazene microsphere solution; S3. Add the second grafting monomer and the catalyst to the polyphosphazene microsphere solution and heat to perform a catalytic reaction to obtain a reaction product, and after washing and drying, obtain the final purified product, i.e., polyphosphazene microspheres grafted with the second grafting monomer having a core-shell structure, which is the first antibacterial agent.

5. The antimicrobial compatibilizer according to claim 4, characterized in that: In S1, the mass ratio of hexachlorocyclotriphosphazene, resveratrol and the second antibacterial agent is 1:(1-3):(1-3); The organic solvent is selected from the group consisting of one or more of tetrahydrofuran, methanol, acetonitrile, ethanol, acetone, N,N-dimethylformamide and N,N-dimethylacetamide; The second antibacterial agent is a nano metal oxide; And / or, the nano metal oxide is any one or more combinations of nano MgO, nano CuO, nano ZnO, and nano TiO2; And / or, in S2, the acid binding agent is selected from one or more of triethylamine, pyridine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, potassium carbonate, ammonium carbonate and sodium carbonate. and / or, in S3, the second grafting monomer is maleic anhydride or cis-1,2,3,6-tetrahydrophthalic anhydride; The catalyst is phthalic acid.

6. A method for preparing an antimicrobial compatibilizer according to any one of claims 1 to 5, characterized in that: The polyolefin elastomer, the first antibacterial agent, the first grafting monomer and the initiator are added to a high-speed mixer and mixed; then the materials are fed to a twin-screw extruder, and the reaction conditions are set to react and extrude; the extrudate is cooled and pelletized to obtain a POE grafted antibacterial agent product, which is an antibacterial compatibilizer.

7. The method for preparing the antimicrobial compatibilizer according to claim 6, characterized in that: In parts by mass, the raw material components are as follows: 100 parts of polyolefin elastomer, 2.5 to 5 parts of the first antibacterial agent, 2.5 to 5 parts of the first grafting monomer, and 0.5 to 1 part of the initiator; The reaction conditions include a reaction temperature of 200-220°C; a screw speed of 200-300 rpm; The feeding speed is 10-20 rpm.

8. Use of the antibacterial compatibilizer according to any one of claims 1 to 5 in the preparation of antibacterial nylon materials.

9. An antibacterial nylon material, characterized in that: The composition comprises at least the antimicrobial compatibility agent as described in any one of claims 1 to 5, nylon and a toughening agent; the toughening agent is glass fiber.

10. The antibacterial nylon material according to claim 9, characterized in that: The antibacterial nylon material comprises, by weight: 50-70 parts of nylon, 25-40 parts of toughening agent, 3-9 parts of antibacterial compatibility agent and 0.2-0.4 parts of antioxidant; The nylon is nylon 66 or nylon 6; the antioxidant is antioxidant 1098.

Citation Information

Patent Citations

  • Polyphosphazene microspheres containing resveratrol units and preparation method thereof

    CN103626804A

  • Nano-silver-loaded polyphosphazene composite antibacterial agent as well as preparation method and application thereof

    CN111248195A

  • Quaternary ammonium salt-loaded polyphosphazene composite antibacterial agent as well as preparation method and application thereof

    CN111328809A

  • Low-temperature-resistant nylon composite material and preparation method thereof

    CN112480643A

  • Silver-loaded polyphosphazene microsphere with mesoporous core-shell structure as well as preparation method and application of silver-loaded polyphosphazene microsphere

    CN112841221A

Cited By

  • TPU compatilizer, TPU master batch, TPU film and preparation method and application thereof

    CN121628007A